CULTURA DE PAZ E EDUCAÇÃO PARA A PAZ: OLHARES A PARTIR DA TEORIA DA COMPLEXIDADE DE EDGAR MORIN - Salles Filho, Nei Alberto (2016)
This paper has as object of research the Education for Peace as an educational component of a Culture of Peace, from the perspective of the Complexity Theory by Edgar Morin. This is a qualitative, exploratory and theoretical research, based on published procedures. The central question of the research, we seek to answer is: What are the theoretical assumptions underlying the Education for Peace, as an educational component of a Culture of Peace, from the perspective of the Complexity Theory by Edgar Morin ? This issue is addressed from supported theoretical questions, such as: a discussion of the Culture for Peace from Edgar Morins´s thoughts, Education for Peace in the context of education in complexity, besides integrated aspects in the constitution of "Five pedagogies of Peace ", consisting of: Education of Human Values, Education of Human rights, Education of Conflicts solving, Education of eco-formation and Education of the Living together. Resulting from these issues, we drew the following research objectives: Build an analytical framework of Education for Peace as a pedagogical way for the Culture of Peace; Discuss the Culture of Peace in relation to the complexity paradigm proposed by Edgar Morin; Relate the Education for Peace to the whole discussion of education in complexity, showing the "seven knowledge for tomorrow's education", proposed by Edgar Morin; Propose an understanding of Education for Peace from the five interconnected components . In this referral, we analyzed the set of six works "Method" by Edgar Morin (2005, 2007, 2008, 2011, 2012, 2013) to understand his world, life, society and education view, which are examined in the sequence of the study. In addition, we analyzed and discussed a theoretical basis for the Education for Peace, especially from the Galtung studies (1994, 2006), Jares (2002, 2007), Rayo (2004) and Serrano (2002). Based on this discussion, the next step of this paper is for the theoretical construction of the "Five Pedagogy of Peace", dealt in their specificity and pedagogical aspects, relating them to the knowledge of education and the perspective of complexity.